XC-skiing under influence of hallux valgus - Scherge, M.; List, S.; Hollenbacher, J. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: The biomechanical relationship between walking and gliding was investigated in an elite-class cross-country skier. A high-resolution pressure measurement plate served as the experimental platform. With additional video analyses, a holistic picture of the biomechanical processes was obtained.